Италмас: поэма / Михаил Петров - Петров Михаил Петрович (Удмуртия, 2000)
Экземпляры: КР (20010428) / Инвентарный номер: у52442 / Цена: 17.00 / Сис.шифр: С(Удм) / Авт.знак: П 30 / ГРНТИ: 17.82 / ББК: 84(2)